Genistein does not inhibit TGF-beta1-induced conversion of human dermal fibroblasts to myofibroblasts - Kaňuchová, M; Urban, L; Melegová, N; Čoma, M; Dvořánková, B; Smetana, Karel; Gál, P (Physiological research, 2021)
Transforming growth factor beta 1 (TGF-beta1) is a pro-fibrotic cytokine with a key role in wound repair and regeneration, including induction of fibroblast-to-myofibroblast transition. Genistein is a naturally occurring selective estrogen receptor modulator with promising anti-fibrotic properties. In the present study we aimed to investigate whether genistein modulates TGF-beta1 (canonical and non-canonical) signaling in normal dermal fibroblasts at the protein level (Western blot and immunofluorescence). We demonstrated that TGF-beta1 induces the myofibroblast-like phenotype in the studied fibroblast signaling via canonical (SMAD) and non-canonical (AKT, ERK1/2, ROCK) pathways. Genistein induced only ERK1/2 expression, whereas the combination of TGF-beta1 and genistein attenuated the ERK1/2 and ROCK signaling. Of note, the other studied pathways remained almost unaffected. From this point of view, genistein does not impair conversion of normal fibroblasts to myofibroblast-like cells.
Keywords: Primary Cell Culture; Genistein; signální transdukce; Signal Transduction; primární buněčná kultura; fibroblasty; genistein; Drug Evaluation, Preclinical; Humans; Phytoestrogens; preklinické hodnocení léčiv; lidé; Transforming Growth Factor beta1; fytoestrogeny; Fibroblasts; transformující růstový faktor beta1